PENGARUH NARSISME TERHADAP ATRIBUSI PEMIMPIN KARISMA DENGAN KUALITAS KOMUNIKASI VISIONER DAN PENGAMBILAN RISIKO SEBAGAI MEDIATOR (STUDI PADA PT TAMAN WISATA CANDI BOROBUDUR, PRAMBANAN DAN RATU BOKO) - Farida, F. Anif (Widya Warta, 2016)
The aim of this research is to determine the effects of narcissism on attribution of charisma leaders with visionary communication quality and risk-taking as mediators. The sample of this study is 80 full-time employees already working not less than 2 years. The analysis made use of Regression analysis technique, t test and F test. The results revealed that narcissism had no effects on communication of socialization vision, but had positive affects on communication of courage vision and risk-taking. Communication of socialization vision had positive affects on attribution of charisma leaders; communication of courage vision had positive effects on attribution of charisma leaders; and, risk-taking had positive affects on attribution of charisma leaders. Communication of socialization vision did not mediate narcissism affects on attribution of charisma leaders; while, communication of courage vision and risk-taking mediated narcissism affets on attribution of charisma leaders.